Urban Raptors Ecology and Conservation of Birds of Prey in Cities (Island Press/Center for Resource Economics, 2018)
Raptors are an unusual success story of wildness thriving in the heart of our cities-they have developed substantial populations around the world in recent decades. But there are deeper issues around how these birds make their urban homes. New research provides insight into the role of raptors as vital members of the urban ecosystem and future opportunities for protection, management, and environmental education. A cutting-edge synthesis of over two decades of scientific research, Urban Raptors is the first book to offer a complete overview of urban ecosystems in the context of bird-of-prey ecology and conservation. This comprehensive volume examines urban environments, explains why some species adapt to urban areas but others do not, and introduces modern research tools to help in the study of urban raptors. It also delves into climate change adaptation, human-wildlife conflict, and the unique risks birds of prey face in urban areas before concluding with real-world wildlife management case studies and suggestions for future research and conservation efforts. Boal and Dykstra have compiled the go-to single source of information on urban birds of prey. Among researchers, urban green space planners, wildlife management agencies, birders, and informed citizens alike, Urban Raptors will foster a greater understanding of birds of prey and an increased willingness to accommodate them as important members, not intruders, of our cities.